2011
DOI: 10.1111/j.1745-4514.2011.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effects of Corn Peptides Against Carbon Tetrachloride-Induced Liver Injury in Mice

Abstract: Hepatic injury is a prevalent ailment worldwide. The hepatoprotective effects of corn peptides (CPs) were evaluated against carbon tetrachloride (CCl4)‐induced liver injury in mice. Low molecular weight CP (Mw < 5 kD) were obtained by alcalase hydrolysis combined with ultrafiltration technology. Results showed that the hepatoprotective effects of CP (200 mg/kg body weight [bw]) were manifested by a significant decrease of the aminotransferase (aspartate transaminase, alanine transaminase) activities in serum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 25 publications
3
36
0
Order By: Relevance
“…14 Our previous studies have confirmed the potent hepatoprotective effect of CPs on acute chemical liver injury induced by CCl 4 , alcohol, and D-galactosamine, [15][16][17] and on the Bacillus CalmetteGuerin/lipopolysaccharide-induced immune liver injury model. 18 It is documented that hepatic fibrosis can be alleviated by bioactive peptides such as carnosine, 19 the vasonatrin peptide originating from animals, 20 and synthetic peptides.…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…14 Our previous studies have confirmed the potent hepatoprotective effect of CPs on acute chemical liver injury induced by CCl 4 , alcohol, and D-galactosamine, [15][16][17] and on the Bacillus CalmetteGuerin/lipopolysaccharide-induced immune liver injury model. 18 It is documented that hepatic fibrosis can be alleviated by bioactive peptides such as carnosine, 19 the vasonatrin peptide originating from animals, 20 and synthetic peptides.…”
Section: Introductionsupporting
confidence: 66%
“…30,31 CPs have a potent antioxidant activity, suggesting potential hepatoprotective effects on acute chemical liver injury in mice. 15 In this study, the antifibrotic effect of CPs might be associated with their antioxidative capability.…”
Section: Discussionmentioning
confidence: 98%
“…There are three known metabolic enzyme systems that participate in the oxidation of alcohol, and all of them lead to over‐production of reactive oxygen species . It was reported that CPs that facilitate alcohol metabolism activity had good hydroxyl radical‐scavenging activity in vitro . Zhuang et al.…”
Section: Resultsmentioning
confidence: 99%
“…Corn protein enzymatic hydrolysate was produced according to the method of Yu et al. . The concentrated corn protein powder (40 g) was reconstituted with water (1000 mL) at a 1:25 ratio (w/v), and incubated in a 100°C water bath for 30 min to denature the corn protein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation